Empowering minds: Exploring the Impact of AI in Facilitating Inclusive Education for Students with Intellectual Disabilities - Marwan Alatawi (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
This experimental research investigated the impact of artificial intelligence (AI) on inclusive education for students with intellectual disabilities. Employing a mixed-methods approach, the study enrolled a diverse cohort of students from an educational institution in Saudi Arabia. Quantitative analyses, utilizing statistical tools like t-tests and regression analyses, assessed the statistical significance of AI interventions on academic outcomes. Concurrently, qualitative insights were gleaned from in-depth interviews and focus group discussions with students and educators revealing nuanced perspectives on engagement, social interactions, and emotional well-being. The findings underscore the multifaceted impact of AI interventions, revealing improvements in academic performance, increased retention rates, and enhanced social integration. This study contributes nuanced insights to the discourse on AI in inclusive education.